DESIGNING NOVEL NANOMATERIALS FOR Li-ION BATTERIES: A PHYSICO-CHEMICAL STUDY THROUGH HYDROGEN-POWERED HORIZONS - Mollaamin, Fatemeh (Jomard Publishing, 2024)
This research work intends to represent a comprehensive investigation on hydrogen grabbing by Si5O10–Ge5O10 was carried out including using density functional theory (DFT) computations. The data represents that if silicon elements are replaced by germanium, the H-grabbing energy will be ameliorated. Electromagnetic and thermodynamic properties of Si5O10–Ge5O10, Li2[Si5O10–Ge5O10] and nanoclusters have been evaluated. The hypothesis of the hydrogen adsorption phenomenon was confirmed by density distributions of charge density differences (CDD), total density of states (TDOS) and localized orbital locator (LOL) for hydrated nanoclusters of H2[Si5O10–Ge5O10] and Li2H4[Si5O10–Ge5O10]. The fluctuation in charge density values demonstrates that the electronic densities were mainly located in the boundary of adsorbate/adsorbent atoms during the adsorption status. Therefore, by combination of Si5O10 and Ge5O10, it can be concluded that Si5O10–Ge5O10 nanocluster might be appropriate candidate for hydrogen storage in transistors. The fluctuation in charge density values demonstrates that the electronic densities were mainly located in the boundary of adsorbate/adsorbent atoms during the adsorption status. As the advantages of lithium over Si/Ge possess its higher electron and hole motion, allowing lithium instruments to operate at higher frequencies than Si/Ge instruments.